ACCOUNTABILITY OF VILLAGE GOVERNANCE IN REALIZING SELF SUFFICIENT VILLAGES: A CASE STUDY OF VILLAGE-OWNED ENTERPRISES - Komalasari, Devi; Akbar, Muhamad; Qomaruddin, Muhammad; Sutarih, Ayih; Gunawan, Moh.Sigit (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2024)
The legal framework governing BUMDes is outlined in Law No. 6 of 2014 concerning Villages, designating BUMDes as business entities. Subsequently, Law No. 11 of 2020 on Job Creation and its derivative, Government Regulation No. 11 of 2021 on Village-Owned Enterprises, specify that BUMDes is a legal entity. However, in Cirebon Regency appears to be a perceptual misalignment or lack of synchronization between information disseminated on social media platforms and the actual status of BUMDes. The research objectives are to analyze the accountability of village governance in improving the form of Village-Owned Enterprises and their accountability in fostering selfsufficient villages. Employing a juridical-empirical research methodology, the study reveals a discrepancy between information circulated on social media and the actual situation. In reality, there are two forms of BUMDes in Cirebon Regency: those with legal standing and those without. Specifically, there are 68 legally recognized BUMDes and 344 non-legally recognized BUMDes out of a total of 412 villages in the region. In conclusion, variations in data and responsibilities are observed within village governance. The coexistence of legally recognized and nonlegally recognized BUMDes leads to divergent management approaches and accountabilities for the villages.